Advanced Transmission Electron Microscopy (Applications to Nanomaterials) - Deepak, Francis Leonard (Springer, 2015)
The book entitled Advanced Transmission Electron Microscopy: Applications to Nanomaterials is an effort to try to bring an update in the field of nanomaterials that have been explored employing state-of-the-art electron microscopic techniques. Electron microscopy has undergone remarkable changes since the invention of the transmission electron microscope (TEM) in 1931 by Max Knoll and Ernst Ruska (Nobel Prize in Physics 1986). The invention of the TEM was a major significant effort to move forward, in terms of spatial resolution, from optical microscopes that were predominant in that era. The efforts and achievements in the field of aberration corrected microscopes would not have happened today if not for the vision of Otto Scherzer who predicted that the limiting factor in the resolution of the microscopes originated from spherical and chromatic aberrations (Spherical and Chromatic Correction of Electron Lenses, Optik, 1947 and J. Appl. Phys., 1949). The dream of imaging atoms without the “blur” of the optics owes its efforts to several people and projects in this field. The importance on several such developments and building of new prototype corrector optics as well as providing the theoretical and experimental understanding towards achieving atomic resolution has been highlighted with the award of the Wolf prize in Physics (2011) to Harald Rose, Maximilian Haider, and Knut Urban....